Phase I Study of Sorafenib and Vorinostat in Advanced Hepatocellular Carcinoma. (August 2019) - Gordon, Sarah W.; McGuire, William P.; Shafer, Danielle A.; Sterling, Richard K.; Lee, Hannah M.; Matherly, Scott C.; Roberts, John D.; Bose, Prithviraj; Tombes, Mary B.; Shrader, E. Ellen; Ryan, Alison A.; Kmieciak, Maciej; et al.
Abstract : Objectives: Preclinical data suggest histone deacetylase inhibitors improve the therapeutic index of sorafenib. A phase I study was initiated to establish the recommended phase 2 dose of sorafenib combined with vorinostat in patients with unresectable hepatocellular carcinoma. Materials and Methods: Patients received vorinostat (200 to 400 mg by mouth once daily, 5 of 7 d) and sorafenib at standard or reduced doses (400 mg [cohort A] or 200 mg [cohort B] by mouth twice daily). Patients who received 14 days of vorinostat in cycle 1 were evaluable for dose-limiting toxicity (DLT). Results: Sixteen patients were treated. Thirteen patients were evaluable for response. Three patients experienced DLTs, 2 in cohort A (grade [gr] 3 hypokalemia; gr 3 maculopapular rash) and 1 in cohort B (gr 3 hepatic failure; gr 3 hypophosphatemia; gr 4 thrombocytopenia). Eleven patients required dose reductions or omissions for non-DLTtoxicity. Ten patients (77%) had stable disease (SD). The median treatment duration was 4.7 months for response-evaluable patients. One patient with SD was on treatment for 29.9 months, and another patient, also with SD, was on treatment for 18.7 months. Another patient electively stopped therapy after 15 months and remains without evidence of progression 3 years later. Conclusions: Although some patients had durable disease control, the addition of vorinostat to sorafenib led to toxicities in most patients, requiring dose modifications that prevented determination of the recommended phase 2 dose. The combination is not recommended for further exploration with this vorinostat schedule in this patient population. Abstract : Supplemental Digital Content is available in the text.